Simvastatin Enhances Activity and Trafficking of α7 Nicotinic Acetylcholine Receptor in Hippocampal Neurons Through PKC and CaMKII Signaling Pathways - Chen, Tingting; Wang, Ya; Zhang, Tingting; Zhang, Baofeng; Chen, Lei; Zhao, Liandong; Chen, Ling (Frontiers in Pharmacology, 2018)
Simvastatin (SV) enhances glutamate release and synaptic plasticity in hippocampal CA1 region upon activation of α7 nicotinic acetylcholine receptor (α7nAChR). In this study, we examined the effects of SV on the functional activity of α7nAChR on CA1 pyramidal cells using patch-clamp recording and explored the underlying mechanisms. We found that the treatment of hippocampal slices with SV for 2 hours induced a dose-dependent increase in the amplitude of ACh-evoked inward currents (IACh) and the level of α7nAChR protein on the cell membrane without change in the level of α7nAChR phosphorylation. These SV-induced phenotypes were suppressed by addition of farnesol (FOH) that converts farnesyl pyrophosphate, but not geranylgeraniol. Similarly, the farnesyl transferase inhibitor FTI277 was able to increase the amplitude of IACh and enhance the trafficking of α7nAChR. The treatment with SV enhanced phosphorylation of CaMKII and PKC. The SV-enhanced phosphorylation of CaMKII rather than PKC was blocked by FOH, Src inhibitor PP2 or NMDA receptor antagonist MK801 and mimicked by FTI. The SV-enhanced phosphorylation of PKC was sensitive to the IP3R antagonist 2-APB. The SV-increased amplitude of IACh was suppressed by PKC inhibitor GF109203X and Go6983, or CaMKII inhibitor KN93. The SV- and FTI-enhanced trafficking of α7nAChR was sensitive to KN93, but not GF109203X or Go6983. The PKC activator PMA increased α7nAChR activity, but had no effect on trafficking of α7nAChR. Collectively, these results indicate that acute treatment with SV enhances the activity and trafficking of α7nAChR by increasing PKC phosphorylation and reducing farnesyl-pyrophosphate to trigger NMDA receptor-mediated CaMKII activation.